2019
DOI: 10.1038/s41598-019-41296-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low and moderate refractive errors on chromatic pupillometry

Abstract: Chromatic pupillometry is an emerging modality in the assessment of retinal and optic nerve disorders. Herein, we evaluate the effect of low and moderate refractive errors on pupillary responses to blue- and red-light stimuli in a healthy older population. This study included 139 participants (≥50 years) grouped by refractive error: moderate myopes (>−6.0D and ≤−3.0D, n = 24), low myopes (>−3.0D and <−0.5D, n = 30), emmetropes (≥−0.5D and ≤0.5D, n = 31) and hyperopes (>0.5D and <6.0D, n = 54). Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…31,33,37 Using a similar light paradigm, we have also reported that the PLR is unaffected by mild or moderate myopia. 39 Taken together, our results suggest that HCP using a ramping-up light paradigm can potentially be used to detect glaucoma in populations with a high prevalence of myopia, such as those in East Asia. 25…”
Section: Discussionsupporting
confidence: 56%
“…31,33,37 Using a similar light paradigm, we have also reported that the PLR is unaffected by mild or moderate myopia. 39 Taken together, our results suggest that HCP using a ramping-up light paradigm can potentially be used to detect glaucoma in populations with a high prevalence of myopia, such as those in East Asia. 25…”
Section: Discussionsupporting
confidence: 56%
“…These findings differ from those of Zhao et al (12) and Yao et al (18), who reported that halo size was only related to minimum pupil diameter under the same condition. Although pupillary responses might not be influenced by refractive errors (26)(27)(28), differences in pupil size (initial pupil diameter, pupil maxima, pupil minima, and average pupil diameter) among the three studies could be responsible for the difference. The pupil size, as controlled by the pupillary light reflex, determines both retinal illuminance and image quality (29).…”
Section: Discussionmentioning
confidence: 88%
“…It has yet to be determined whether cPLR could also be used to evaluate the efficacy of gene therapy in achromatopsia patients. It is noteworthy that cPLR testing has also been reported in ametropic patients, and it has been demonstrated that constriction to bright red light is most significant in hyperopes 85,86 .…”
Section: Discussionmentioning
confidence: 97%